Teachers Teaching Management During Belajar dari Rumah (BDR) Policy In Higher Education: A Piece of Teacher Sharing Ways - Suryawahyuni Latief; Santi Hendrayani; Samsuddin Samsuddin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2021)
Teaching is an educator activity in the learning process, which aims to develop the potential that students have in the form of knowledge, skills, and attitudes. Since the Covid 19 pandemic, the government has issued a policy of